2003
DOI: 10.1177/073401680302800106
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Police Education in Handling Cases of Mental Disorder

Abstract: This article considers the impact of police officers' education in relation to a single type of"critical incident," one in which suspects appeared to be mentally ill. Data are taken from interviews of officers with three different levels of education: high school only, some college or university, and a university degree. The research considers whether officers with different educational levels reported handling cases differently, after controlling for officers' gender, age, and experience, in addition to suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
2
9
0
1
Order By: Relevance
“…This suggests that depending on the symptoms exhibited by a person experiencing mental illness, these negative characteristics might also be associated with restrictive outcomes. These findings are consistent with previous research that found that police officer decision making was related to inferences regarding a suspect's dangerousness and, furthermore, officers' endorsement of restrictive treatment options (LaGrange, 2003;Watson et al, 2004). Similarly, Mendias and Kehoe (2006) reported that officers who believe their role is primarily to enforce the law will be more likely to resort to arrest.…”
Section: Discriminating Outcomes To Scenariossupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that depending on the symptoms exhibited by a person experiencing mental illness, these negative characteristics might also be associated with restrictive outcomes. These findings are consistent with previous research that found that police officer decision making was related to inferences regarding a suspect's dangerousness and, furthermore, officers' endorsement of restrictive treatment options (LaGrange, 2003;Watson et al, 2004). Similarly, Mendias and Kehoe (2006) reported that officers who believe their role is primarily to enforce the law will be more likely to resort to arrest.…”
Section: Discriminating Outcomes To Scenariossupporting
confidence: 93%
“…Also of interest to researchers have been offenders' mental state, gender, and race (Finn & Stalans, 1997;Smith, Visher, & Davidson, 1984) and the knowledge, exp erience, and education of police officers regarding working with people who are mentally ill (Green, 1997;LaGrange, 2003;Patch & Arrigo, 1999;Teplin, 2000;Watson, Corrigan, & Ottati, 2004). More recently, researchers have become interested in the influence of police officers' attitudes regarding mental illness.…”
mentioning
confidence: 98%
“…An integral element of policing-in both enforcement based and community based response models-is responding to PIC. Many academic studies have identified that frontline police officers acknowledge that responding to PIC is a significant part of their job (Borum et al, 1998;Hartford et al, 2006;Cooper et al, 2004;Cotton, 2004;Godfredson et al, 2011;LaGrange, 2003;Sellers et al, 2005;Senior et al, 2014). Borum and colleagues (1998) characterise this increased attention to responding to PIC as the 'quiet revolution' in policing.…”
Section: Policing and Mental Healthmentioning
confidence: 99%
“…One of the most important factors to consider when discussing police-based responses to PIC is the amount of training officers receive. The academic literature consistently argues that police officers do not feel adequately trained to respond to the needs of PIC (Bittner, 1967;Borum et al, 1998;Cooper et al, 2004;Cotton, 2004;Godfredson et al, 2011;Hails & Borum, 2003;Hartford et al, 2006;LaGrange, 2003;Sellers et al, 2005Senior et al, 2014. In addition, Senior and colleagues (2014) report that officers felt there were little or no opportunities to update or learn new skills once they are operational (i.e., in the field responding to PIC).…”
Section: Policing and Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation